Modification of the drug resistance of emerging milk-borne pathogens through sodium alginate-based antibiotics and nanoparticles - Manan, Abdul; Aqib, Amjad Islam; Shahbaz, Ansa; Khan, Shanza Rauf; Akram, Kashif; Majeed, Hamid; Muneer, Afshan; Murtaza, Maheen; Afrasiab, Muhammad; Merola, Carmine; Niaz, Kamal; Ahmad, Irfan; et al. (Frontiers in Veterinary Science, 2023)
Streptococcus agalactiae and Klebsiella pneumoniae are emerging as major milk-borne pathogens. Additionally, resistance to antibiotics of pathogens is of concern. Therefore, this study investigated the prevalence and drug resistance of S. agalactiae and K. pneumoniae in mastitis milk samples and assessed the antimicrobial potential of sodium alginate (G)-stabilized MgO nanoparticles (M) and antibiotics (tylosin [T] and ampicillin [A]) against both of these pathogens. A total of n = 200 milk samples from cattle were collected using purposive sampling, and standard microbiological approaches were adopted to isolate target bacteria. Parametric and non-parametric statistical tests were used to analyze the obtained data. Four preparations, GT (gel-stabilized tylosin), GA (gel-stabilized ampicillin), GTM (tylosin and MgO nanoparticles stabilized in gel), and GAM (ampicillin and MgO nanoparticles stabilized in gel), were evaluated against both bacteria through well diffusion and broth microdilution method. The analysis revealed that 45.24% (95/210) of the milk samples were positive for mastitis, of which 11.58% (11/95) were positive for S. agalactiae and 9.47% (9/95) were positive for K. pneumoniae. S. agalactiae had a significantly higher zone of inhibition (ZOI) than K. pneumoniae against penicillin, tetracycline, and amoxicillin, whereas the opposite was observed against imipenem and erythromycin. All gel (G)-based preparations showed an increase in the percentage of ZOI compared with antibiotics alone, with GTM presenting the highest of all, i.e., 59.09 and 56.25% ZOI compared with tylosin alone against S. agalactiae and K. pneumoniae, respectively. Similarly, in a broth microdilution assay, the lowest MIC was found for K. pneumoniae (9.766 ± 0.0 μg/mL) against GTM, followed by GT, GAM, and GA after incubation for 24 h. A similar response was noted for preparations against S. agalactiae but with a comparatively higher MIC. A significant reduction in MIC with respect to incubation time was found at 8 h and remained until at 20 h against both pathogens. The cytotoxicity of the MgO nanoparticles used in this study was significantly lower than that of the positive control. Overall, this study found that K. pneumoniae and S. agalactiae appeared higher in prevalence and antimicrobial resistance, and sodium alginate-based antibiotics and MgO nanoparticles were effective alternative approaches for tackling antimicrobial resistance.